Analisis Kompetensi Literasi Media Sosial pada Mahasiswa Perpustakaan dan Sains Informasi Universitas Padjadjaran dalam Konsumsi Informasi di Instagram - Azzahra, Tsabitah Siti; Khadijah, Ute Lies Siti; Saepudin, Encang (UPT Perpustakaan UIN Alauddin Makassar, 2025)
This study aims to determine the social media literacy skills of Library and Information Science students at Padjadjaran University in consume an information on Instagram. The research method is quantitative with a descriptive approach with probability sampling, it is stratified random sampling. The data collection techniques used are interviews, questionnaires, and literature studies. The questionnaire was distributed to 75 students from the 2022–2024 batch. The results of the study show that overall, students have good social media literacy skills in terms of consuming information on Instagram. However, there are still a small number of students who have low contribution skills. Therefore, there is still a need to improve social media literacy skills, especially in terms of contribution skills, in order to respond optimally to information consumption.